A Comparative Religious Concepts: Gender Equality in Islam and Buddha (Journal Intellectual Sufism Research (JISR), 2024)
This research is based on the author's discontent with the problems of inter-religious conflicts that frequently occur within communities. These issues often arise from mutual ignorance, leading to misunderstandings and triggering conflicts. The problems do not stop at violent conflicts but also intersect with gender issues, which still frequently occur, especially among minority communities. The role of religion itself becomes vital and urgent in raising awareness among its followers about what they collectively believe in. Therefore, it is hoped that this writing can present a new perspective that, both in Islam and Buddhism, there is an equal emphasis on the fair role of gender in the context of social life.